Development of a Learning Management Model for Scouts and Girl Guides Based on the Principles of the King's Philosophy to Enhance Life Skills for Undergraduate Students at the Thailand National Sports University - Leelert, Thanit; Pengkeantao, Surawut (Journal of Buddhist Education and Research (JBER), 2025)
This study aimed to develop a learning management model for Scout and Red Cross Youth activities based on the principles of the King’s Philosophy and to evaluate its effects on the life skills of undergraduate students at the National Sports University. The research employed a Research and Development (R&D) methodology, consisting of three phases: reviewing related theories and literature, developing the learning management model, and implementing and evaluating the model. The sample consisted of 60 undergraduate students enrolled in the Scout and Red Cross Youth course, selected through simple random sampling. Research instruments included questionnaires, behavioral observation forms, and life skills tests. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics with a dependent t-test. The developed model integrated the Philosophy of Sufficiency Economy with experiential learning, emphasizing self-reliance, teamwork, leadership, and social engagement. Learning activities included project-based learning, volunteer service, and simulated leadership training. The results showed that after using the model, students' life skills significantly improved in all aspects - from a level requiring development to good or excellent levels. These findings indicate that the model effectively enhanced students’ life skills. The study recommends expanding the model to other educational institutions, providing teacher training, and conducting further research to explore long-term outcomes and applications in diverse contexts.